Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

The Rotokawa geothermal system, New Zealand: Hydrothermal minerals and punctuated evolution - Mark P. Simpson; Amando G. Morales; Isabelle Chambefort; Samantha Alcaraz; Shunsuke Moribe; Sarah D. Milicich; Fabian Sepulveda; Jeffrey W. Hedenquist (Journal of Volcanology and Geothermal Research, 2026)

Early warning signs: Applications of in vivo NMR spectroscopy to understand the impacts of industrial effluents - Kiera Ronda; Sequoia Thompson; Peter M. Costa; William W. Wolff; Katelyn Downey; Owen Vander Meulen; Daniel H. Lysak; Jacob Pellizzari; Katrina Steiner; Daniel Lane; Carlos Cobas; Santiago Domínguez; et al. (Aquatic Toxicology, 2026)

Mass timber wall splice connection using glued-in rods: Design methodology, implementation, and shake-table testing in a six-story building - Steven Kontra; Andre R. Barbosa; Arijit Sinha; Steve Pryor; Reid B. Zimmerman; Barbara Simpson; John W. van de Lindt; Shiling Pei; Gustavo A. Araújo R.; Morgan McBain; Ludovica Pieroni; Prashanna Mishra; et al. (Engineering Structures, 2026)

Considering the evolutionary benefits and costs of friendship networks - Grace Vieth; Ryan Dobson; Steven W. Gangestad; Jeffry A. Simpson (Evolution and Human Behavior, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Surface characteristics limit the vertical mobility of an invasive reptile - Thomas W. Simpson; Marleen Baling; Anne C. Gaskett; Richard C. Gibson; Steven Matthews; Jacqueline R. Beggs (Biological Invasions, 2026)
Preventing the spread of small, cryptic invasive reptiles poses an ongoing challenge for conservation and biosecurity worldwide. Physical exclusion barriers offer a potentially low-cost, non-toxic tool for limiting dispersal, but their effectiveness depends on, among other factors, a detailed understanding of how surface properties influence animal movement. We tested four commonly available fencing materials—polypropylene fabric, woven polypropylene, polythene sheet, and acrylic sheet—as potential barriers to climbing by a small Australian skink, Lampropholis delicata (Scincidae). Experiments with 18 adult skinks were conducted in enclosures under both wet and dry conditions. We quantified surface roughness using four metrics: arithmetic average roughness (Ra), total height of profile (Rt), mean spacing of profile irregularities (Rsm) and Skewness (Rsk). Climbing frequency was highest on the roughest material, polypropylene fabric (Ra = 25, Rt = 167, Rsm = 457.5 µm), with up to 60% of individuals climbing. In contrast, the smoother surfaces, polythene and acrylic, limited climbing to just 5% of trials, with climbs occurring only under wet conditions. This suggests that surface water may enhance adhesion and reduce the effectiveness of smooth barriers. Our findings indicate that simple vertical drift fences are unlikely to effectively manage the spread of L. delicata , particularly in wet environments and underscore the importance of incorporating surface roughness thresholds and moisture conditions into barrier design. Polythene sheet, shows promise for indoor containment but would require modifications such as anti-climb lips for outdoor use. Tailored exclusion strategies that integrate material science with animal behaviour and ecological context could offer scalable, environmentally friendly tools for containing and managing invasive species.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Scope effects and willingness to pay for deep sea management practices within and beyond national jurisdictions - Bui Bich Xuan; Claire W. Armstrong; Stephen Hynes; Isaac Ankamah-Yeboah; Katherine Simpson; Godwin K. Vondolia (Journal of Environmental Management, 2025)

Supplementation strategies to control propionic acid accumulation resulting from ammonia inhibition in dry anaerobic digestion: Osmoprotectants, activated carbon and trace elements - Ildefonso Rocamora; Stuart T. Wagland; Francis Hassard; Raffaella Villa; Miriam Peces; Ioannis A. Fotidis; Edmon W. Simpson; Oliver Fernández; Yadira Bajón-Fernández (Journal of Environmental Chemical Engineering, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Association of physical function with connectivity in the sensorimotor and dorsal attention networks: why examining specific components of physical function matters - Madeline C. Boyd; Jonathan H. Burdette; Michael E. Miller; Robert G. Lyday; Christina E. Hugenschmidt; W. Jack Rejeski; Sean L. Simpson; Laura D. Baker; Chal E. Tomlinson; Stephen B. Kritchevsky; Paul J. Laurienti (GeroScience, 2024)
Declining physical function with aging is associated with structural and functional brain network organization. Gaining a greater understanding of network associations may be useful for targeting interventions that are designed to slow or prevent such decline. Our previous work demonstrated that the Short Physical Performance Battery (eSPPB) score and body mass index (BMI) exhibited a statistical interaction in their associations with connectivity in the sensorimotor cortex (SMN) and the dorsal attention network (DAN). The current study examined if components of the eSPPB have unique associations with these brain networks. Functional magnetic resonance imaging was performed on 192 participants in the BNET study, a longitudinal and observational trial of community-dwelling adults aged 70 or older. Functional brain networks were generated for resting state and during a motor imagery task. Regression analyses were performed between eSPPB component scores (gait speed, complex gait speed, static balance, and lower extremity strength) and BMI with SMN and DAN connectivity. Gait speed, complex gait speed, and lower extremity strength significantly interacted with BMI in their association with SMN at rest. Gait speed and complex gait speed were interacted with BMI in the DAN at rest while complex gait speed, static balance, and lower extremity strength interacted with BMI in the DAN during motor imagery. Results demonstrate that different components of physical function, such as balance or gait speed and BMI, are associated with unique aspects of brain network organization. Gaining a greater mechanistic understanding of the associations between low physical function, body mass, and brain physiology may lead to the development of treatments that not only target specific physical function limitations but also specific brain networks.

Contractile vacuoles: a rapidly expanding (and occasionally diminishing?) understanding - Kiran J. More; Harpreet Kaur; Alastair G.B. Simpson; Frederick W. Spiegel; Joel B. Dacks (European Journal of Protistology, 2024)

Olfactory tract/bulb metal concentration in Manganese-exposed mineworkers - Luis F. Gonzalez-Cuyar; Gill Nelson; Susan Searles Nielsen; Wendy W. Dlamini; Amelia Keyser-Gibson; C. Dirk Keene; Michael Paulsen; Susan R. Criswell; Natalie Senini; Lianne Sheppard; Shar Samy; Christopher D. Simpson; et al. (NeuroToxicology, 2024)

Description and taxonomic assessment of fossil Cercopithecidae from the Pliocene Galili Formation (Ethiopia) - Hailay G. Reda; Stephen R. Frost; Evan A. Simons; Jay Quade; Scott W. Simpson (Journal of Human Evolution, 2024)

Analysis of natural organic matter chemistry in bentonite clay under compaction using different dry densities and duration - Meiling Man; Huan Tong; Nivetha Srikanthan; Muhammed O. Usman; Claire S. Tully; James J. Noël; Mehran Behazin; W. Jeffrey Binns; Peter G. Keech; Myrna J. Simpson (Applied Geochemistry, 2024)

Randomized trial in rural Native American homes heated with wood stoves: results from the EldersAIR study - Curtis W. Noonan; Ethan S. Walker; Erin O. Semmens; Annie Belcourt; Johna Boulafentis; Crissy Garcia; Jon Graham; Nolan Hoskie; Eugenia Quintana; Julie Simpson; Paul Smith; Howard L. Teasley; et al. (Air Quality, Atmosphere & Health, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Monitoring the use of novel psychoactive substances in Australia by wastewater-based epidemiology - Emma L. Jaunay; Richard Bade; Kara R. Paxton; Dhayaalini Nadarajan; Daniel C. Barry; Yuze Zhai; Benjamin J. Tscharke; Jake W. O'Brien; Jochen Mueller; Jason M. White; Bradley S. Simpson; Cobus Gerber (Science of The Total Environment, 2024)

Current extent and future opportunities for living shorelines in Australia - Rebecca L. Morris; Erin Campbell-Hooper; Elissa Waters; Melanie J. Bishop; Catherine E. Lovelock; Ryan J. Lowe; Elisabeth M.A. Strain; Paul Boon; Anthony Boxshall; Nicola K. Browne; James T. Carley; Benedikt J. Fest; et al. (Science of The Total Environment, 2024)

Anthropogenic, biogenic, and photochemical influences on surface formaldehyde and its significant decadal (2006–2017) decrease in the Lewiston-Clarkston valley of the northwestern United States - R. Li; B.T. Jobson; M. Wen; A.L. Li; Y. Huangfu; W. Zhang; R. Hardy; P. O'Keeffe; J. Simpson; M. Fauci; N. Paden (Chemosphere, 2024)

Zebrafish cardiac repolarization does not functionally depend on the expression of the hERG1b-like transcript - Christine E. Genge; Padmapriya Muralidharan; Jake Kemp; Christina M. Hull; Mandy Yip; Kyle Simpson; Diana V. Hunter; Thomas W. Claydon (Pflügers Archiv - European Journal of Physiology, 2024)

Acoustic backscattering at a tidal intrusion front - Christopher Bassett; Andone C. Lavery; David Ralston; W. Rockwell Geyer; Joseph T. Jurisa; Jim Thomson; David A. Honegger; Alexandra Simpson; Malcom E. Scully; Merrick C. Haller (Progress in Oceanography, 2023)

Modulating Cortical Hemodynamic Activity in Parkinson’s Disease Using Focal Transcranial Direct Current Stimulation: A Pilot Functional Near-infrared Spectroscopy Study - Michael W Simpson; Margaret Mak (Brain Topography, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The role of acoustics within the sensory landscape of coral larval settlement - Josh W. Pysanczyn; Elizabeth A. Williams; Emelie Brodrick; Daniel Robert; Jamie Craggs; Kristen L. Marhaver; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Recruitment of coral larvae on reefs is crucial for individual survival and ecosystem integrity alike. Coral larvae can detect and respond to a wide range of biotic and abiotic cues, including acoustic cues, to locate suitable sites for settlement and metamorphosis. However, the acoustic ecology of coral larvae, including how they perceive auditory cues, remains poorly understood. In this mini-review we consider both ex situ physiology and behavior, and in situ ecological and behavioral studies, to first provide an updated overview of the abiotic and biotic cues used by coral larvae to guide settlement. We then explore in detail the use of acoustic cues and the current literature on behavioral responses to acoustic stimuli. Finally, we discuss gaps in our understanding of the mechanisms by which coral larvae detect acoustic cues, highlighting a novel application of technology to explore these sensory capabilities. We also address how larval phonotaxis, i.e., the ability to orient to a sound cue, can be applied to coral reef conservation. Current research suggests that acoustic cues are likely used at small spatial scales, and that coral larvae may have directional acoustic sensitivity enabling phonotactic behavior. Recruitment of coral larvae on reefs is significantly influenced by habitat-specific soundscape variation and likely affected by anthropogenic disturbance. We propose a novel application of the remote sensing technology, micro-scanning laser Doppler vibrometry (LDV), to quantify the micromechanical responses of putative acoustically sensitive epidermal microstructures. We then highlight the potential for incorporation of acoustic enrichment techniques in coral reef conservation and restoration interventions.

Inhibitory mechanisms on dry anaerobic digestion: Ammonia, hydrogen and propionic acid relationship - Ildefonso Rocamora; Stuart T. Wagland; Francis Hassard; Raffaella Villa; Miriam Peces; Edmon W. Simpson; Oliver Fernández; Yadira Bajón-Fernández (Waste Management, 2023)

Genome screening, reporting, and genetic counseling for healthy populations - Selina Casalino; Erika Frangione; Monica Chung; Georgia MacDonald; Sunakshi Chowdhary; Chloe Mighton; Hanna Faghfoury; Yvonne Bombard; Lisa Strug; Trevor J. Pugh; Jared Simpson; Saranya Arnoldo; et al. (Human Genetics, 2023)

Profile likelihood-based parameter and predictive interval analysis guides model choice for ecological population dynamics - Matthew J. Simpson; Shannon A. Walker; Emma N. Studerus; Scott W. McCue; Ryan J. Murphy; Oliver J. Maclaren (Mathematical Biosciences, 2023)

Optimization and Scale Up of Spray Dried CPZEN-45 Aerosol Powders for Inhaled Tuberculosis Treatment - Ian E. Stewart; Phillip G. Durham; Jacob M. Sittenauer; Aranza P. Barreda; Grayson W. Stowell; Carmella Moody; Jeffery B. Mecham; Catherine Simpson; Sharon Daily; Sara E. Maloney; Mark D. Williams; Diana Severynse-Stevens; et al. (Pharmaceutical Research, 2022)

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Spatiotemporal Patterns in the Biomass of Drift Macroalgae in the Indian River Lagoon, Florida, United States - Lauren M. Hall; Lori J. Morris; Robert H. Chamberlain; M. Dennis Hanisak; Robert W. Virnstein; Richard Paperno; Bernhard Riegl; L. Rex Ellis; Ali Simpson; Charles A. Jacoby (Frontiers in Marine Science, 2022)
Drift macroalgae plays key roles in the ecology of many coastal systems, including the Indian River Lagoon. In the lagoon, changes in the biomass of drift macroalgae may have interacted with an unprecedented bloom of phytoplankton in 2011. Patterns in the biomass of drift macroalgae were identified using new and original analyses of data from several sampling programs collected between 1997 and 2019. All available data show a relatively low biomass of drift macroalgae in 2010–2012, and surveys of fixed transects and seining as part of a fisheries independent monitoring program also recorded low biomass in 2016. Low light availability and potentially stressful temperatures appeared to be the main influences as indicated by the results of incubations in tanks to determine environmental tolerances and data on ambient conditions. Decreased biomass of drift macroalgae had implications for cycling of nutrients because carbon, nitrogen, and phosphorus not stored in the tissues of drift macroalgae became available for uptake by other primary producers, including phytoplankton. The estimated 14–18% increases in concentrations of these elements in the IRL could have promoted longer and more intense phytoplankton blooms, which would have reduced light availability and increased stress on algae and seagrasses. An improved understanding of such feedback and the ecological roles played by drift macroalgae will support more effective management of nutrient loads and the system by accounting for cycling of nutrients among primary producers.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Bird rookery nutrient over-enrichment as a potential accelerant of mangrove cay decline in Belize - L. T. Simpson; S. W. J. Canty; J. R. Cissell; M. K. Steinberg; J. A. Cherry; I. C. Feller (Oecologia, 2021)

A method and its application to determine the amount of cannabinoids in sewage sludge and biosolids - Aaron J. Pandopulos; Bradley S. Simpson; Richard Bade; Jake W. O’Brien; Meena K. Yadav; Jason M. White; Cobus Gerber (Environmental Science and Pollution Research, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

The quorum‐sensing systems of Vibrio campbellii DS40M4 and BB120 are genetically and functionally distinct - Chelsea A. Simpson; Blake D. Petersen; Nicholas W. Haas; Logan J. Geyman; Aimee H. Lee; Ram Podicheti; Robert Pepin; Laura C. Brown; Douglas B. Rusch; Michael P. Manzella; Kai Papenfort; Julia C. van Kessel (Environmental Microbiology, 2021)
Summary Vibrio campbellii BB120 (previously classified as Vibrio harveyi ) is a fundamental model strain for studying quorum sensing in vibrios. A phylogenetic evaluation of sequenced Vibrio strains in Genbank revealed that BB120 is closely related to the environmental isolate V. campbellii DS40M4. We exploited DS40M4's competence for exogenous DNA uptake to rapidly generate greater than 30 isogenic strains with deletions of genes encoding BB120 quorum‐sensing system homologues. Our results show that the quorum‐sensing circuit of DS40M4 is distinct from BB120 in three ways: (i) DS40M4 does not produce an acyl homoserine lactone autoinducer but encodes an active orphan LuxN receptor, (ii) the quorum regulatory small RNAs (Qrrs) are not solely regulated by autoinducer signalling through the response regulator LuxO and (iii) the DS40M4 quorum‐sensing regulon is much smaller than BB120 (~100 genes vs. ~400 genes, respectively). Using comparative genomics to expand our understanding of quorum‐sensing circuit diversity, we observe that conservation of LuxM/LuxN proteins differs widely both between and within Vibrio species. These strains are also phenotypically distinct: DS40M4 exhibits stronger interbacterial cell killing, whereas BB120 forms more robust biofilms and is bioluminescent. These results underscore the need to examine wild isolates for a broader view of bacterial diversity in the marine ecosystem.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Root proliferation and phosphorus acquisition in response to stratification of soil phosphorus by two contrasting Trifolium subterraneum cultivars - Jonathan W. McLachlan; Richard J. Flavel; Chris N. Guppy; Richard J. Simpson; Rebecca E. Haling (Plant and Soil, 2020)

Can we project changes in fish abundance and distribution in response to climate? - Jose A. Fernandes; Louise Rutterford; Stephen D. Simpson; Momme Butenschön; Thomas L. Frölicher; Andrew Yool; William W. L. Cheung; Alastair Grant (Global Change Biology, 2020)
Large‐scale and long‐term changes in fish abundance and distribution in response to climate change have been simulated using both statistical and process‐based models. However, national and regional fisheries management requires also shorter term projections on smaller spatial scales, and these need to be validated against fisheries data. A 26‐year time series of fish surveys with high spatial resolution in the North‐East Atlantic provides a unique opportunity to assess the ability of models to correctly simulate the changes in fish distribution and abundance that occurred in response to climate variability and change. We use a dynamic bioclimate envelope model forced by physical–biogeochemical output from eight ocean models to simulate changes in fish abundance and distribution at scales down to a spatial resolution of 0.5°. When comparing with these simulations with annual fish survey data, we found the largest differences at the 0.5° scale. Differences between fishery model runs driven by different biogeochemical models decrease dramatically when results are aggregated to larger scales (e.g. the whole North Sea), to total catches rather than individual species or when the ensemble mean instead of individual simulations are used. Recent improvements in the fidelity of biogeochemical models translate into lower error rates in the fisheries simulations. However, predictions based on different biogeochemical models are often more similar to each other than they are to the survey data, except for some pelagic species. We conclude that model results can be used to guide fisheries management at larger spatial scales, but more caution is needed at smaller scales.

Energetic Carrying Capacity of Submersed Aquatic Vegetation in Semi-Permanent Wetlands Important to Waterfowl in the Upper Midwest - Margaret C. Gross; Joseph D. Lancaster; John W. Simpson; Brendan T. Shirkey; Sarah E. McClain; Christopher N. Jacques; J. Brian Davis; Heath M. Hagy (Wetlands, 2020)

Root proliferation in response to P stress and space: implications for the study of root acclimation to low P supply and P acquisition efficiency - Jonathan W. McLachlan; Rebecca E. Haling; Richard J. Simpson; Richard J. Flavel; Chris N. Guppy (Plant and Soil, 2020)

Climate warming alters subsoil but not topsoil carbon dynamics in alpine grassland - Juan Jia; Zhenjiao Cao; Chengzhu Liu; Zhenhua Zhang; Li Lin; Yiyun Wang; Negar Haghipour; Lukas Wacker; Hongyan Bao; Thorston Dittmar; Myrna J. Simpson; Huan Yang; et al. (Global Change Biology, 2019)
Subsoil contains more than half of soil organic carbon (SOC) globally and is conventionally assumed to be relatively unresponsive to warming compared to the topsoil. Here, we show substantial changes in carbon allocation and dynamics of the subsoil but not topsoil in the Qinghai‐Tibetan alpine grasslands over 5 years of warming. Specifically, warming enhanced the accumulation of newly synthesized ( 14 C‐enriched) carbon in the subsoil slow‐cycling pool (silt‐clay fraction) but promoted the decomposition of plant‐derived lignin in the fast‐cycling pool (macroaggregates). These changes mirrored an accumulation of lipids and sugars at the expense of lignin in the warmed bulk subsoil, likely associated with shortened soil freezing period and a deepening root system. As warming is accompanied by deepening roots in a wide range of ecosystems, root‐driven accrual of slow‐cycling pool may represent an important and overlooked mechanism for a potential long‐term carbon sink at depth. Moreover, given the contrasting sensitivity of SOC dynamics at varied depths, warming studies focusing only on surface soils may vastly misrepresent shifts in ecosystem carbon storage under climate change.

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

The error in stream sediment phosphorus fractionation and sorption properties effected by drying pretreatments - Zachary P. Simpson; Richard W. McDowell; Leo M. Condron (Journal of Soils and Sediments, 2019)

The influence of a flood event on the potential sediment control of baseflow phosphorus concentrations in an intensive agricultural catchment - Richard W. McDowell; Zach P. Simpson; Roland Stenger; Craig Depree (Journal of Soils and Sediments, 2019)

Draft genome sequence of the symbiotic Frankia sp. strain BMG5.30 isolated from root nodules of Coriaria myrtifolia in Tunisia - Abdellatif Gueddou; Erik Swanson; Karima Hezbri; Imen Nouioui; Amir Ktari; Stephen Simpson; Krystalynne Morris; W. Kelley Thomas; Faten Ghodhbane-Gtari; Maher Gtari; Louis S. Tisa (Antonie van Leeuwenhoek, 2019)

Identification of powdery mildew resistance QTL in strawberry (Fragaria × ananassa) - Helen M. Cockerton; Robert J. Vickerstaff; Amanda Karlström; Fiona Wilson; Maria Sobczyk; Joe Q. He; Daniel J. Sargent; Andy J. Passey; Kirsty J. McLeary; Katalin Pakozdi; Nicola Harrison; Maria Lumbreras-Martinez; et al. (Theoretical and Applied Genetics, 2018)

Environmental exposure and parental collection does not affect detection or semi-quantitative load assessment of bacteria in nasal swab specimens from children - Nada Townsi; Shannon J. Simpson; Chisha T. Sikazwe; Glenys R. Chidlow; Graham L. Hall; J. Jane Pillow; Andrew C. Wilson; David W. Smith; Ingrid A. Laing (Infectious Diseases, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Localised hydrodynamics influence vulnerability of coral communities to environmental disturbances - George Shedrawi; James L. Falter; Kim J. Friedman; Ryan J. Lowe; Morgan S. Pratchett; Christopher J. Simpson; Conrad W. Speed; Shaun K. Wilson; Zhenlin Zhang (Coral Reefs, 2017)

Time Dependent Behaviour of Trabecular Bone at Multiple Load Levels - Shuqiao Xie; Krishnagoud Manda; Robert J. Wallace; Francesc Levrero-Florencio; A. Hamish R. W. Simpson; Pankaj Pankaj (Annals of Biomedical Engineering, 2017)

Mapping and expression of genes associated with raspberry fruit ripening and softening - Craig G. Simpson; Danny W. Cullen; Christine A. Hackett; Kay Smith; Paul D. Hallett; Jim McNicol; Mary Woodhead; Julie Graham (Theoretical and Applied Genetics, 2017)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Detecting Extinction Risk from Climate Change by IUCN Red List Criteria - DAVID A. KEITH; MICHAEL MAHONY; HARRY HINES; JANE ELITH; TRACEY J. REGAN; JOHN B. BAUMGARTNER; DAVID HUNTER; GEOFFREY W. HEARD; NICOLA J. MITCHELL; KIRSTEN M. PARRIS; TRENT PENMAN; BEN SCHEELE; et al. (Conservation Biology, 2014)
Anthropogenic climate change is a key threat to global biodiversity. To inform strategic actions aimed at conserving biodiversity as climate changes, conservation planners need early warning of the risks faced by different species. The IUCN Red List criteria for threatened species are widely acknowledged as useful risk assessment tools for informing conservation under constraints imposed by limited data. However, doubts have been expressed about the ability of the criteria to detect risks imposed by potentially slow‐acting threats such as climate change, particularly because criteria addressing rates of population decline are assessed over time scales as short as 10 years. We used spatially explicit stochastic population models and dynamic species distribution models projected to future climates to determine how long before extinction a species would become eligible for listing as threatened based on the IUCN Red List criteria. We focused on a short‐lived frog species (Assa darlingtoni) chosen specifically to represent potential weaknesses in the criteria to allow detailed consideration of the analytical issues and to develop an approach for wider application. The criteria were more sensitive to climate change than previously anticipated; lead times between initial listing in a threatened category and predicted extinction varied from 40 to 80 years, depending on data availability. We attributed this sensitivity primarily to the ensemble properties of the criteria that assess contrasting symptoms of extinction risk. Nevertheless, we recommend the robustness of the criteria warrants further investigation across species with contrasting life histories and patterns of decline. The adequacy of these lead times for early warning depends on practicalities of environmental policy and management, bureaucratic or political inertia, and the anticipated species response times to management actions. Detección del Riesgo de Extinción a partir del Cambio Climático por medio del Criterio de la Lista Roja de la UICNKeith et al.

Challenges in understanding the sources of bioaccumulated metals in biota inhabiting turbid river systems - Tom Cresswell; Ross E. W. Smith; Stuart L. Simpson (Environmental Science and Pollution Research, 2014)

Mechanisms driving an unusual latitudinal diversity gradient for grasses - Vernon Visser; W. Derek Clayton; David A. Simpson; Robert P. Freckleton; Colin P. Osborne (Global Ecology and Biogeography, 2014)
Aim For most higher‐order taxa, species diversity peaks sharply in the moist tropics and declines rapidly at higher latitudes. However, the mechanisms driving this latitudinal gradient are numerous, remain uncertain and are even undocumented in some important major clades such as the grasses. Grasses are a cosmopolitan, important plant family with more than 11,000 species world‐wide. Our aims were: to investigate the latitudinal distributions of species richness for different grass lineages, and the grass family as a whole; and to test hypotheses proposed in general for the latitudinal diversity gradient or specifically as determinants of grass species richness patterns at the global scale. Location Global. Methods We used the most comprehensive global database of grass distributions currently available to calculate species richness for 340 political regions of the world. Using generalized additive models we used these data to model the latitudinal gradients of species richness for different grass lineages and for the grass family as a whole. We constructed multiple regression models to include climatic, productivity, topographic, habitat and geographic variables. Results An unusual, shallow latitudinal diversity gradient arises because different grass lineages exhibit contrasting latitudinal patterns. This reflects differential specialization of grass lineages to arid and cool environments, the legacy of historical effects, most notably the Gondwanan origin of the grasses, and a strong association between grasses and topographically heterogeneous, mountainous regions. Main conclusions The grasses are one of the relatively few higher‐order lineages that exhibits an atypical latitudinal gradient; this has arisen because of climatic specialization of particular grass lineages to cold and arid environments. Key additional roles have been inferred for historical biogeography and topographical heterogeneity in determining global patterns of grass species richness. These mechanisms have generally been under‐appreciated and are probably important for many other lineages.

Challenges with tracing the fate and speciation of mine-derived metals in turbid river systems: implications for bioavailability - Tom Cresswell; Ross E. W. Smith; Dayanthi Nugegoda; Stuart L. Simpson (Environmental Science and Pollution Research, 2013)

Arthropod food webs become increasingly lipid‐limited at higher trophic levels - Shawn M. Wilder; Michael Norris; Raymond W. Lee; David Raubenheimer; Stephen J. Simpson (Ecology Letters, 2013)
Understanding why food chains are relatively short in length has been an area of research and debate for decades. We tested if progressive changes in the nutritional content of arthropods with trophic position limit the availability of a key nutrient, lipid, for carnivores. Arthropods at higher trophic levels had progressively less lipid and more protein in their bodies compared with arthropods at lower trophic levels. The nutrients present in arthropod bodies were directly related to the nutrients that predators extracted when feeding on those arthropods. As a consequence, nutrient assimilation shifted from lipid‐biased to protein‐biased as arthropods ascended trophic levels from herbivores to secondary carnivores. Successive changes in the nutritional consequences of predation may ultimately set an upper limit on the number of trophic levels in arthropod communities. Further work is needed to examine the influence of lipid and other nutrients on food web traits in a range of ecosystems.

A new species of Kolpochoerus (Mammalia: Suidae) from the Pliocene of Central Afar, Ethiopia: Its Taxonomy and Phylogenetic Relationships - Yohannes Haile-Selassie; Scott W. Simpson (Journal of Mammalian Evolution, 2013)

Erratum to: GLP-1-dependent and independent effects and molecular mechanisms of a dipeptidyl peptidase 4 inhibitor in vascular endothelial cells - Yunshan Hu; HongBin Liu; Richard W. Simpson; Anthony E. Dear (Molecular Biology Reports, 2013)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

Notes on the health status of free-living, non-native American mink, Neovison vison, in southern England - L. A. Harrington; M. Gelling; V. Simpson; A. Harrington; D. W. Macdonald (European Journal of Wildlife Research, 2012)

Serum skeletal troponin I following inspiratory threshold loading in healthy young and middle-aged men - Glen E. Foster; Jiro Nakano; A. William Sheel; Jeremy A. Simpson; Jeremy D. Road; W. Darlene Reid (European Journal of Applied Physiology, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Assessment of airborne Asteraceae pollen in Brisbane, Australia - Brett J. Green; Rod W. Simpson; Mary E. Dettmann (Aerobiologia, 2012)

A microsatellite linkage map for the cultivated strawberry (Fragaria × ananassa) suggests extensive regions of homozygosity in the genome that may have resulted from breeding and selection - D. J. Sargent; T. Passey; N. Šurbanovski; E. Lopez Girona; P. Kuchta; J. Davik; R. Harrison; A. Passey; A. B. Whitehouse; D. W. Simpson (Theoretical and Applied Genetics, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

A test of the senses: Fish select novel habitats by responding to multiple cues - Chantal M. Huijbers; Ivan Nagelkerken; Pauline A. C. Lössbroek; Ines E. Schulten; Andjin Siegenthaler; Marc W. Holderied; Stephen D. Simpson (Ecology, 2012)
Habitat‐specific cues play an important role in orientation for animals that move through a mosaic of habitats. Environmental cues can be imprinted upon during early life stages to guide later return to adult habitats, yet many species must orient toward suitable habitats without previous experience of the habitat. It is hypothesized that multiple sensory cues may enable animals to differentiate between habitats in a sequential order relevant to the spatial scales over which the different types of information are conveyed, but previous research, especially for marine organisms, has mainly focused on the use of single cues in isolation. In this study, we investigated novel habitat selection through the use of three different sensory modalities (hearing, vision, and olfaction). Our model species, the French grunt, Haemulon flavolineatum , is a mangrove/seagrass‐associated reef fish species that makes several habitat transitions during early life. Using several in situ and ex situ experiments, we tested the response of fish toward auditory, olfactory, and visual cues from four different habitats (seagrass beds, mangroves, rubble, and coral reef). We identified receptivity to multiple sensory cues during the same life phase, and found that different cues induced different reactions toward the same habitat. For example, early‐juvenile fish only responded to sound from coral reefs and to chemical cues from mangroves/seagrass beds, while visual cues of conspecifics overruled olfactory cues from mangrove/seagrass water. Mapping these preferences to the ecology of ontogenetic movements, our results suggest sequential cue use would indeed aid successful orientation to novel key habitats in early life.

Enzymatic Characterisation of USP7 Deubiquitinating activity and Inhibition - Jonathan D. Wrigley; Kay Eckersley; Ian M. Hardern; Lindsey Millard; Michael Walters; Stephen W. Peters; Richard Mott; Thorsten Nowak; Richard A. Ward; Peter B. Simpson; Kevin Hudson (Cell Biochemistry and Biophysics, 2011)

Defining reference conditions and restoration targets for lake ecosystems using palaeolimnology: a synthesis - Helen Bennion; Richard W. Battarbee; Carl D. Sayer; Gavin L. Simpson; Thomas A. Davidson (Journal of Paleolimnology, 2011)

A palaeolimnological meta-database for assessing the ecological status of lakes - Richard W. Battarbee; David Morley; Helen Bennion; Gavin L. Simpson; Michael Hughes; Viktorija Bauere (Journal of Paleolimnology, 2011)

A reference typology of low alkalinity lakes in the UK based on pre-acidification diatom assemblages from lake sediment cores - Richard W. Battarbee; Gavin L. Simpson; Helen Bennion; Christopher Curtis (Journal of Paleolimnology, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

Laboratory Animal Management Assistant (LAMA): a LIMS for active research colonies - Marko Milisavljevic; Taryn Hearty; Tony Y. T. Wong; Elodie Portales-Casamar; Elizabeth M. Simpson; Wyeth W. Wasserman (Mammalian Genome, 2010)

Paleolimnological evidence of the effects on lakes of energy and mass transfer from climate and humans - Peter R. Leavitt; S. C. Fritz; N. J. Anderson; P. A. Baker; T. Blenckner; L. Bunting; J. Catalan; D. J. Conley; W. O. Hobbs; E. Jeppesen; A. Korhola; S. McGowan; et al. (Limnology and Oceanography, 2009)
The premise of this article is that climate effects on lakes can be quantified most effectively by the integration of process‐oriented limnological studies with paleolimnological research, particularly when both disciplines operate within a common conceptual framework. To this end, the energy (E)‐mass ( m ) flux framework (E m flux) is developed and applied to selected retrospective studies to demonstrate that climate variability regulates lake structure and function over diverse temporal and spatial scales through four main pathways: rapid direct transfer of E to the lake surface by irradiance, heat, and wind; slow indirect effects of E via changes in terrestrial development and subsequent m subsidies to lakes; direct influx of m as precipitation, particles, and solutes from the atmosphere; and indirect influx of water, suspended particles, and dissolved substances from the catchment. Sedimentary analyses are used to illustrate the unique effects of each pathway on lakes but suggest that interactions among mechanisms are complex and depend on the landscape position of lakes, catchment characteristics, the range of temporal variation of individual pathways, ontogenetic changes in lake basins, and the selective effects of humans on m transfers. In particular, preliminary synthesis suggests that m influx can overwhelm the direct effects of E transfer to lakes, especially when anthropogenic activities alter m subsidies from catchments.

Renal injury at first presentation as a predictor for poor outcome in severe paracetamol poisoning referred to a liver transplant unit - N. Pakravan; K. J. Simpson; W. S. Waring; C. M. Bates; D. N. Bateman (European Journal of Clinical Pharmacology, 2009)

What is a Genus in Cypereae: Phylogeny, Character Homology Assessment and Generic Circumscription in Cypereae - A. Muthama Muasya; Alexander Vrijdaghs; David A. Simpson; Mark W. Chase; Paul Goetghebeur; Erik Smets (The Botanical Review, 2009)

Phylogeny of Cyperaceae Based on DNA Sequence Data: Current Progress and Future Prospects - A. Muthama Muasya; David A. Simpson; G. Anthony Verboom; Paul Goetghebeur; Robert F. C. Naczi; Mark W. Chase; Erik Smets (The Botanical Review, 2009)

Development of “universal” gene-specific markers from Malus spp. cDNA sequences, their mapping and use in synteny studies within Rosaceae - Daniel J. Sargent; Annalisa Marchese; David W. Simpson; Werner Howad; Felicidad Fernández-Fernández; Amparo Monfort; Pere Arús; Kate M. Evans; Kenneth R. Tobutt (Tree Genetics & Genomes, 2009)

A simple method for the production of bacterial controls for immunohistochemistry and fluorescent in situ hybridization - Camilla Recordati; Enrico Radaelli; Kenneth W. Simpson; Eugenio Scanziani (Journal of Molecular Histology, 2008)

Taxonomic novelties in Rhynchospora (Cyperaceae) from South America - A. C. Araújo; H. M. Longhi-Wagner; W. W. Thomas; D. A. Simpson (Kew Bulletin, 2008)

A Bayesian palaeoenvironmental transfer function model for acidified lakes - Philip B. Holden; Anson W. Mackay; Gavin L. Simpson (Journal of Paleolimnology, 2008)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

The Role of Multiphosphorylated Peptides in Mineralized Tissue Regeneration - Keith J. Cross; N. Laila Huq; Neil M. O’Brien-Simpson; John W. Perich; Troy J. Attard; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2007)

Effects of Light on Microalgae Concentrations and Selenium Uptake in Bivalves Exposed to Selenium-Amended Sediments - D. Schlenk; G. Batley; C. King; J. Stauber; M. Adams; S. Simpson; W. Maher; J. T. Oris (Archives of Environmental Contamination and Toxicology, 2007)

The development and mapping of functional markers in Fragaria and their transferability and potential for mapping in other genera - D. J. Sargent; A. Rys; S. Nier; D. W. Simpson; K. R. Tobutt (Theoretical and Applied Genetics, 2006)

An enhanced microsatellite map of diploid Fragaria - D. J. Sargent; J. Clarke; D. W. Simpson; K. R. Tobutt; P. Arús; A. Monfort; S. Vilanova; B. Denoyes-Rothan; M. Rousseau; K. M. Folta; N. V. Bassil; N. H. Battey (Theoretical and Applied Genetics, 2006)

A note on the relationship between temperature and water vapor over oceans, including sea surface temperature effects - C. -L. Shie; W. -K. Tao; J. Simpson (Advances in Atmospheric Sciences, 2006)

Encapsulation of protein nanoparticles into uniform-sized microspheres formed in a spinning oil film - W. Thomas Leach; Dale T. Simpson; Tibisay N. Val; Zhongshui Yu; Kwon T. Lim; Eun J. Park; Robert O. Williams; Keith P. Johnston (AAPS PharmSciTech, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

A genetic linkage map of microsatellite, gene-specific and morphological markers in diploid Fragaria - D. J. Sargent; T. M. Davis; K. R. Tobutt; M. J. Wilkinson; N. H. Battey; D. W. Simpson (Theoretical and Applied Genetics, 2004)

Sound-evoked vestibulo-ocular reflexes (VOR) in trained monkeys - Wu Zhou; W. Mustain; I. Simpson (Experimental Brain Research, 2004)

Plant collecting spread and densities: their potential impact on biogeographical studies in Thailand - J. A. N. Parnell; D. A. Simpson; J. Moat; D. W. Kirkup; P. Chantaranothai; P. C. Boyce; P. Bygrave; S. Dransfield; M. H. P. Jebb; J. Macklin; C. Meade; D. J. Middleton; et al. (Journal of Biogeography, 2003)
Aims To produce representative aggregate maps of plant collection locations in Thailand and discuss their impact on biogeographical studies in Thailand and the surrounding region. Location Thailand. Methods A representative data set comprising 6593 plant specimen records for Thailand has been assembled. The data set contains ± all known collections for fifteen representative plant families and further records for another 104. All records are localized to Changwat (province), 6441 to at least quarter degree square. Results Analysis shows that the spread of collecting activity in Thailand is markedly uneven; 20% of collections come from a single Changwat (Chiang Mai) and 53% of Changwat have fifty or fewer collections. The distribution of collections by Changwat and by quarter degree square is erratic with most squares and Changwat having few collections, both in proportionate and absolute terms. Some of the most densely forested Changwats and squares appear undercollected. Distribution maps for common, easily recognized tree species in the genus Syzygium show distributional gaps. Conclusions Thailand is defined as an undercollected country. Even within the few well‐collected quarter degree squares the spread of collecting is still poor; almost all collections being localized to one of three mountain ranges or their foothills. There are many gaps in collecting activity which make impossible a straightforward interpretation of biogeographical pattern. It is argued that targeted collecting activity is needed, that assembly of this type of data set is therefore essential and that our data set and its interpretation is a model for all countries in the region.

Expression of a Truncated Brca1 Protein Delays Lactational Mammary Development in Transgenic Mice - Melissa A. Brown; Hans Nicolai; Kathy Howe; Toyomasa Katagiri; El-Nasir Lalani; Kaylene J. Simpson; Nathan W. Manning; Andrew Deans; Phil Chen; Kum Kum Khanna; Mas Rina Wati; Beatrice L. Griffiths; et al. (Transgenic Research, 2002)

Towards A Long-Term Integrated Monitoring Programme In Europe: Network Design in Theory and Practice - T. W. Parr; M. Ferretti; I. C. Simpson; M. Forsius; E. Kovács-Láng (Environmental Monitoring and Assessment, 2002)

Maristentor dinoferus n. gen., n. sp., a giant heterotrich ciliate (Spirotrichea: Heterotrichida) with zooxanthellae, from coral reefs on Guam, Mariana Islands - Lobban C.; Schefter M.; Simpson A.; Pochon X.; Pawlowski J.; Foissner W. (Marine Biology, 2002)

Maristentor dinoferus n. gen., n. sp., a giant heterotrich ciliate (Spirotrichea: Heterotrichida) with zooxanthellae, from coral reefs on Guam, Mariana Islands - Lobban C.; Schefter M.; Simpson A.; Pochon X.; Pawlowski J.; Foissner W. (Marine Biology, 2002)

Simulation of mixing depths incorporating the urban heat island effect - Suhail M. Khan; Rod W. Simpson (Environmental Modeling & Assessment, 2001)

Effect Of A Heat Island On The Meteorology Of A Complex Urban Airshed - Suhail M. Khan; Rod W. Simpson (Boundary-Layer Meteorology, 2001)

Energy model for contrast detection: spatiotemporal characteristics of threshold vision - V. Manahilov; W. Simpson (Biological Cybernetics, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

The Validity of Similarity Theory in the Roughness Sublayer Above Forests - I. J. Simpson; G. W. Thurtell; H. H. Neumann; G. Den Hartog; G. C. Edwards (Boundary-Layer Meteorology, 1998)

On the role of ?hot towers? in tropical cyclone formation - J. Simpson; J. B. Halverson; B. S. Ferrier; W. A. Petersen; R. H. Simpson; R. Blakeslee; S. L. Durden (Meteorology and Atmospheric Physics, 1998)

An assessment of suprageneric phylogeny inCyperaceae usingrbcL DNA sequences - Abraham M. Muasya; David A. Simpson; Mark W. Chase; Alastair Culham (Plant Systematics and Evolution, 1998)

Mesoscale trajectory modeling for the Brisbane airshed - Suhail M. Khan; Rod W. Simpson (Environmental Modeling & Assessment, 1997)

Modelling mixing height from routinely measured surface and upper air meteorological data - Suhail M. Khan; Rod W. Simpson (Environmental Modeling & Assessment, 1997)

Polypedilum digitifer Townes andPolypedilum griseopunctatum (Malloch) (Diptera, Chironomidae): Redescription of adult males with a description and separation of the immature stages - Annelle R. Soponis; Karl W. Simpson (Aquatic Ecology, 1992)

Annual report from the Editorial Office of the American Potato Journal - Geddes W. Simpson; Donald C. Nelson (American Journal of Potato Research, 1984)

Book review: Potato diseases - F. E. Manzer; G. W. Simpson (American Journal of Potato Research, 1984)

Annual report of the Editor-in-Chief - Geddes W. Simpson (American Journal of Potato Research, 1983)

Report of the Editor-in-Chief July 1981 through June 1982 - Geddes W. Simpson (American Journal of Potato Research, 1982)

Effect of time of inoculation with potato leafroll virus on development of net necrosis and stem-end browning in potato tubers - F. E. Manzer; D. C. Merriam; R. H. Storch; G. W. Simpson (American Journal of Potato Research, 1982)

American Potato Journal report of the Editor-in-Chief July 1980 through June 1981 - Geddes W. Simpson (American Journal of Potato Research, 1981)

Congo/Crimean Haemorrhagic Fever virus from Iraq 1979: I. Morphology in BHK21 cells - D. S. Ellis; T. Southee; G. Lloyd; G. S. Platt; Nicola Jones; Susan Stamford; E. T. W. Bowen; D. I. H. Simpson (Archives of Virology, 1981)

American Potato Journal Report of the Editor-in-Chief July 1979 through June 1980 - Geddes W. Simpson (American Journal of Potato Research, 1980)

American Potato Journal report of the Editor-in-Chief July 1978 through June 1979 - Geddes W. Simpson (American Journal of Potato Research, 1979)

American Potato Journal report of the Editor-in-Chief July 1977 thru june 1978 - Geddes W. Simpson (American Journal of Potato Research, 1978)

Erlon L. Newdick 1888–1975 - Paul J. Eastman; Geddes W. Simpson (American Journal of Potato Research, 1975)

Spraying potatoes to prevent leaf roll spread by the green peach aphid - W. A. Shands; Geddes W. Simpson (American Journal of Potato Research, 1972)

Growth characteristics of potato plants useful in studies of population dynamics and biological control of aphids - W. A. Shands; G. W. Simpson; Corinne C. Gordon (American Journal of Potato Research, 1971)

Bioenvironmental control of the green peach aphid,Myzus persicae - W. A. Shands; Geddes W. Simpson (American Journal of Potato Research, 1969)

Penobscot: A new variety of potato with leafroll resistance and high solids - G. W. Simpson; R. V. Akeley (American Journal of Potato Research, 1964)

Exploratory tests to prevent leaf roll infection transmitted by aphids - W. A. Shands; G. W. Simpson (American Journal of Potato Research, 1964)

The relationship of aphid abundance on potato plants to the specific gravity of the tubers - W. A. Shands; G. W. Simpson (American Journal of Potato Research, 1962)

Report of editorial committee - Arthur Hawkins; Ora Smith; A. Frank Ross; R. E. Webb; G. W. Simpson; J. C. Campbell (American Journal of Potato Research, 1959)

The use of ethylene chlorohydrin for breaking the rest period of large quantities of potatoes - W. F. Porter; G. W. Simpson (American Journal of Potato Research, 1947)